Wnt-7a Stimulates Dendritic Spine Morphogenesis and PSD-95 Expression Through Canonical Signaling - Ramos-Fernandez, Eva; Tapia-Rojas, Cheril; Ramirez, Valerie T.; Inestrosa, Nibaldo C. (My University, 2019)
Wnt signaling regulates brain development and synapse maturation; however, the precise molecular mechanism remains elusive. Here, we report that Wnt-7a stimulates dendritic spine morphogenesis in the hippocampus via glycogen synthase kinase-3 (GSK-3) inhibition, triggering -catenin/T cell factor/lymphoid enhancer factor (TCF/LEF)-dependent gene transcription and promoting postsynaptic density-95 (PSD-95) protein expression. In addition, wild-type mice treated with an inhibitor of -catenin/TCF/LEF-mediated transcription showed a reduction in spatial memory acquisition accompanied by a reduction in PSD-95 and decreases in spine density measured by Golgi staining, suggesting that PSD-95 is a novel Wnt target gene. Together, our data strongly demonstrate that Wnt-dependent target gene transcription is essential to hippocampal synaptic plasticity.
Keywords: wnt signaling; dendritic spine plasticity; psd-95; tcf; lef